2010
DOI: 10.1029/2009wr007810
|View full text |Cite
|
Sign up to set email alerts
|

Linking hierarchical stratal architecture to plume spreading in a Lagrangian‐based transport model: 2. Evaluation using new data from the Borden site

Abstract: [1] A new data set collected at the well-documented Borden research site was used in order to evaluate a newly published but as yet untested idea for stochastic modeling (Ramanathan et al., 2008). The new data set reveals the stratal architecture of the Borden aquifer and allowed us to determine how the stratal architecture, at different scales, controlled the macrodispersion observed in the original natural gradient tracer test. The newly published idea for modeling uses a Lagrangian-based model for the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…[43] The interpretive modeling exercise showed that the horizontal Ä autosemivariogram and the Ä-Y cross-semivariogram are defined more by the cross transitions than the cross transitions, as previously shown for the horizontal Y autocovariance [Ramanathan et al, 2010]. The cross-transition structure is, in turn, mostly defined by the proportions and the mean and variance in lengths of level II units.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…[43] The interpretive modeling exercise showed that the horizontal Ä autosemivariogram and the Ä-Y cross-semivariogram are defined more by the cross transitions than the cross transitions, as previously shown for the horizontal Y autocovariance [Ramanathan et al, 2010]. The cross-transition structure is, in turn, mostly defined by the proportions and the mean and variance in lengths of level II units.…”
Section: Discussionmentioning
confidence: 88%
“…The composite horizontal integral scales for the YY h À Á , ÄÄ h À Á , and ÄY h À Á models are, respectively, 1.9, 1.8, and 2.0. Note, the A-D terms in Table 3 are derived from data only at locations where k and K d measurements are both located, and not being restricted by this, Ramanathan et al [2010] used slightly more k data in defining A-D terms for a horizontal Y autocovariance model. Their A-D values have negligible differences (i.e., in the fourth and fifth significant figures) from those reported here, and give the same composite Y integral scale of 1.9 m. Note also that the data from horizontal lines of sampling at x k locations in Figure 1 do not facilitate an analysis of the study of vertical sample semivariograms (for Y or Ä).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations